A "Yin"-"Yang" complementarity strategy for design and fabrication of dual-responsive bimorph actuators. (February 2020) - Zhang, Yong-Lai; Ma, Jia-Nan; Liu, Sen; Han, Dong-Dong; Liu, Yu-Qing; Chen, Zhao-Di; Mao, Jiang-Wei; Sun, Hong-Bo
Abstract: Multi-responsive soft actuators that can convert environmental energies to mechanical works are promising for robotics. However, it currently lacks universal and effective concepts to develop dual-responsive bimorph actuators. In this paper, the concept of "Yin"-"Yang" complementarity, a classical theory in the history of Chinese philosophy, has been adopted for designing dual-responsive actuators. The complement of "Yin" and "Yang" means the bilayers can be inter-constraint as well as being complementary in a dual-responsive actuation. As a proof-of-concept, a composite layer of nano-size graphite (Nano-G) and polyvinylidene fluoride (PVDF) has been combined with graphene oxide (GO), forming a bilayer structure. In response to moisture, GO is positive, meaning "Yang", whereas Nano-G@PVDF is negative, meaning "Yin". On the contrary, under light irradiation, GO is negative; whereas the photothermal Nano-G@PVDF layer is positive. We demonstrated a bi-directional walking robot and a smart claw array for controllable moisture/light manipulation. The "Yin"-"Yang" complementarity strategy provides a universal concept for developing multi-responsive bimorph actuators. Graphical abstract: Image 1 Highlights: The concept of "Yin"-"Yang" complementarity has been adopted as a universal principle for designing dual-responsive actuators. A composite layer of nano-size graphite (Nano-G) and PVDF has been combined with GO, forming a moisture and light dual-responsive bimorph actuator. In response to moisture and light, the GO and Nano-G@PVDF layers are interdependent and inter-constraint as well as being complementary. A bi-directional walking robot and a smart claw array for allowing moisture/light manipulation has been fabricated.